2019
DOI: 10.1002/chem.201805256
|View full text |Cite
|
Sign up to set email alerts
|

Radical Carbofluorination of Alkenes with Arylhydrazines and Selectfluor: Additives, Mechanistic Pathways, and Polar Effects

Abstract: Radical carbofluorination reactions starting from arylhydrazines and nonactivated alkenes, in which the C−F bond is formed through the use of Selectfluor, can be improved through the addition of anisole. Because direct trapping products could be detected only in trace amounts, anisole does primarily act as a reversible scavenger for the highly reactive ammonium radical dication released from Selectfluor in the C−F bond‐forming step. As shown for three diverse substitution patterns, the main role of anisole is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…2b Based on this pioneering study, an improved carbofluorination was recently developed, in which the addition of anisole led to a reduced formation of side products (Scheme 21). 71 Scheme 21 Selectfluor-mediated fluoroarylation of non-activated alkenes 71 Similar to the earlier study, Selectfluor (50) serves as an oxidant to generate aryl radicals from phenylhydrazines 48, while phenyldiazenes XXXVIII occur as intermediates. In addition, Selectfluor enables fluorine atom transfer 72 to the alkyl radicals II leading to the carbofluorination products 49 as well as the Selectfluor-derived radical dication XXX-IX.…”
Section: Carbohalogenationmentioning
confidence: 85%
“…2b Based on this pioneering study, an improved carbofluorination was recently developed, in which the addition of anisole led to a reduced formation of side products (Scheme 21). 71 Scheme 21 Selectfluor-mediated fluoroarylation of non-activated alkenes 71 Similar to the earlier study, Selectfluor (50) serves as an oxidant to generate aryl radicals from phenylhydrazines 48, while phenyldiazenes XXXVIII occur as intermediates. In addition, Selectfluor enables fluorine atom transfer 72 to the alkyl radicals II leading to the carbofluorination products 49 as well as the Selectfluor-derived radical dication XXX-IX.…”
Section: Carbohalogenationmentioning
confidence: 85%
“…By judiciously integrating ease of carbon radical generation, through either transition‐metal catalysis or photocatalysis, with productive fluorination techniques, considerable progress has been attained in the arena of fluoroalkylation reactions, although most of the reported methods still show a heavy reliance on electrophilic fluorination reagents . However, the fluoroarylation counterpart is comparatively underdeveloped, probably due to a relative lack of efficient avenues for the easy production of aryl radical intermediates …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, several recent reports also suggested that a tertiary aminium radical derived from Selectuor could also undergo the addition to olens for the catalytic oxidative functionalization of alkenes. [45][46][47] Thus, the quinuclidinium radical intermediate derived from quinuclidine as a tertiary amine should also perform the addition process with olens. In order to detect this mechanistic paradigm, a radical probe experiment was designed.…”
Section: Introductionmentioning
confidence: 99%